A SOCIOLOGICAL STUDY OF EDUCATIONAL LEVEL AND ITS EFFECT ON WOMENS’ HEALTH: A STUDY OF S.A.S NAGAR, MOHALI, PUNJAB - Singh, Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education is the most powerful tool for improving the status of women in society. Women who receive mindfulness training see a noticeable difference in their conceptual and child welfare as compared to unskilled women. The prevalence of social problems pertaining to women is higher in rural areas. These include dowry practices, selling female infants, female infanticide, female feticide, gender inequity, and more. Therefore, it is imperative to regulate these social problems. Enhancing the quality of life for rural women is crucial for this reason. A higher standard of living and education contribute to a reduction in the social ills connected to women's status. Therefore, it is crucial to look into the socio-cultural connection between women's health and educational achievement. The goal of this study is to determine rural women level of education, to evaluate the health of rural women and to understand the relationship between education and health of rural women.